Influence of CSR Transparency and Sustainable Growth on Corporate Economic Performance - Machdar, Nera Marinda; Oktris, Lin (Indonesian Journal of Accounting and Governance, 2024)
This study aims to analyze the effect of corporate social responsibility (CSR) disclosure and sustainable growth on corporate financial and economic performance. The research population comprises all manufacturing firms listed on the Indonesia Stock Exchange over the period 2012–2017. The sample is selected using a purposive sampling method, involving 102 firms, resulting in a total of 612 firm-year observations. This research utilizes secondary data obtained from the Indonesia Stock Exchange and the Indonesian Capital Market Directory. Multiple regression analysis with panel data is employed to test the developed hypotheses. The findings are as follows: (a) CSR disclosure does not affect economic performance; (b) sustainable growth does not affect economic performance; (c) CSR disclosure negatively affects financial performance; and (d) sustainable growth positively affects financial performance. This study provides new insights by specifically focusing on the manufacturing sector within the Indonesian context. Unlike previous studies that generalized findings across various sectors, this research delves into sector-specific impacts, offering more tailored insights for policymakers and corporate managers in the manufacturing industry. Additionally, the study highlights the differential impacts of CSR and sustainable growth on economic and financial performance, underscoring the complexity and multifaceted nature of these variables.